A novel genetic model provides a unique perspective on the relationship between postexercise glycogen concentration and increases in the abundance of key metabolic proteins after acute exercise. - Seong Eun Kwak; Amy Zheng; Edward B Arias; Haiyan Wang; Xiufang Pan; Yongping Yue; Dongsheng Duan; Gregory D Cartee (PLoS ONE)
Some acute exercise effects are influenced by postexercise (PEX) diet, and these diet-effects are attributed to differential glycogen resynthesis. However, this idea is challenging to test rigorously. Therefore, we devised a novel genetic model to modify muscle glycogen synthase 1 (GS1) expression in rat skeletal muscle with an adeno-associated virus (AAV) short hairpin RNA knockdown vector targeting GS1 (shRNA-GS1). Contralateral muscles were injected with scrambled shRNA (shRNA-Scr). Muscles from exercised (2-hour-swim) and time-matched sedentary (Sed) rats were collected immediately postexercise (IPEX), 5-hours-PEX (5hPEX), or 9-hours-PEX (9hPEX). Rats in 5hPEX and 9hPEX experiments were refed (RF) or not-refed (NRF) chow. Muscles were analyzed for glycogen, abundance of metabolic proteins (pyruvate dehydrogenase kinase 4, PDK4; peroxisome proliferator-activated receptor γ coactivator-1α, PGC1α; hexokinase II, HKII; glucose transporter 4, GLUT4), AMP-activated protein kinase phosphorylation (pAMPK), and glycogen metabolism-related enzymes (glycogen phosphorylase, PYGM; glycogen debranching enzyme, AGL; glycogen branching enzyme, GBE1). shRNA-GS1 versus paired shRNA-Scr muscles had markedly lower GS1 abundance. IPEX versus Sed rats had lower glycogen and greater pAMPK, and neither of these IPEX-values differed for shRNA-GS1 versus paired shRNA-Scr muscles. IPEX versus Sed groups did not differ for abundance of metabolic proteins, regardless of GS1 knockdown. Glycogen in RF-rats was lower for shRNA-GS1 versus paired shRNA-Scr muscles at both 5hPEX and 9hPEX. HKII protein abundance was greater for 5hPEX versus Sed groups, regardless of GS1 knockdown or diet, and despite differing glycogen levels. At 9hPEX, shRNA-GS1 versus paired shRNA-Scr muscles had greater PDK4 and PGC1α abundance within each diet group. However, the magnitude of PDK4 or PGC1α changes was similar in each diet group regardless of GS1 knockdown although glycogen differed between paired muscles only in RF-rats. In summary, we established a novel genetic approach to investigate the relationship between muscle glycogen and other exercise effects. Our results suggest that exercise-effects on abundance of several metabolic proteins did not uniformly correspond to differences in postexercise glycogen.